The effect of auriculotherapy on individuals with anxiety in follow-up in Primary Health Care - José Henrique da Silva Cunha; Vandilson Pinheiro Rodrigues; Heloísa Cristina Figueiredo Frizzo; Franciele Kavafara Pires; Amanda Polin Pereira; Francisca Bruna Arruda Aragão; Regina Célia Fiorati (Revista Brasileira de Enfermagem, 2025)
ABSTRACT Objectives: to analyze the effects of auriculotherapy on the mental health of individuals with anxiety in Primary Healthcare. Methods: a sequential explanatory mixed-methods study was conducted with 60 patients from a health unit in Uberaba, MG. Quantitative data were obtained using the DASS-21 and WHOQOL-Bref questionnaires. Qualitative data were collected from 17 semi-structured interviews and analyzed through thematic content analysis. Statistical analysis included the Wilcoxon signed-rank test, paired t-test, and multivariate regression models. Results: after ten sessions of auriculotherapy, anxiety levels decreased, with most participants (86.7%) reaching normal levels. Additionally, 61.7% rated their quality of life as good, and 46.7% reported satisfaction with their health. Six thematic categories emerged. Auriculotherapy reduced DASS-21 scores and WHOQOL-Bref domain scores, even after adjusted analysis. Conclusions: auriculotherapy was effective in reducing anxiety and improving users’ quality of life.